Low dose radiation therapy attenuates ACE2 depression and inflammatory cytokines induction by COVID-19 viral spike protein in human bronchial epithelial cells. (3rd October 2022) - Wen, Ke; Bai, Chenjun; Zhao, Hongling; Zhou, Pingkun; Gao, Shanshan; Guan, Hua; Song, Man
Abstract: Purpose: Low-dose radiation therapy (LDRT) is an evidence-based anti-inflammatory treatment. In anti-COVID-19, our study suggests that low to moderate dose radiation of < 1.5 Gy can inhibit the induction of inflammatory cytokine and attenuate the ACE2 depression induced by spike protein in human bronchial epithelial cells in COVID-19 infection. Our study provided further mechanistic evidence to support LDRT as a cost-effective treatment for COVID-19 to relieve the severe inflammatory reaction and lung injury. Methods and materials: A cellular model was created by treating human bronchial epithelial cells (BEP2D) with SARS-CoV-2 spike protein. We used the qRT-PCR and ELISA analysis to identify the production of inflammatory cytokines. The BEP2D control cells and the spike-treated cells were irradiated using a single low to moderate dose radiation of 0.5 Gy, 1 Gy, and 1.5 Gy. The inflammatory cytokines and ACE2 expression were detected at different time points. Results: The soluble SARS-CoV-2 spike protein stimulated the formation of inflammatory cytokines IL-6 and TNF-α while reducing the ACE2 protein expression in human bronchial epithelial cells. A single low to moderate dose exposure of 0.5 Gy, 1 Gy, and 1.5 Gy could attenuate the IL-6 and TNF-α induction and rescue the depression of ACE2 by spike protein. Moreover, the spike protein increased the proteolytic degradation of ACE2 protein by promoting NEDD4-mediated ubiquitination of ACE2. Conclusions: The low-dose radiation can attenuate ACE2 depression and inflammatory response produced in the targeted human bronchial epithelial cells by spike protein. This coordinating effect of LDRT may relieve the severe inflammatory reaction and lung injury in COVID-19 patients.